2002
DOI: 10.1097/00005392-200204000-00035
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Risk Of Re-Treatment Of Patients Using ??-Blockers For Lower Urinary Tract Symptoms

Abstract: Patients given alpha-blockers for lower urinary tract symptoms have a high risk of re-treatment. Tamsulosin has a markedly lower re-treatment percentage than alfuzosin and terazosin. Severe symptoms, poor urine flow, an enlarged prostate and urodynamically proven bladder outlet obstruction increase the risk of treatment failure. Preselection of the most suitable candidates for alpha-blockade may reduce this risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
2
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 11 publications
2
48
2
4
Order By: Relevance
“…8 A similar result was reported where the discontinuation rates were 64% after 3 years and 79% after 5 years of follow up after administration of a1-blockers. 13 Thus, all men who receive a1-blockers do not necessarily continue the same medication for a long time. However, the patients who could continue tamsulosin showed durable symptomatic improvement for 5 years, as shown in several previous reports.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…8 A similar result was reported where the discontinuation rates were 64% after 3 years and 79% after 5 years of follow up after administration of a1-blockers. 13 Thus, all men who receive a1-blockers do not necessarily continue the same medication for a long time. However, the patients who could continue tamsulosin showed durable symptomatic improvement for 5 years, as shown in several previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…20 Several static and dynamic variables to predict treatment failure and conversion to surgery of a1-blockers have been reported. 5,8,13,14,21 De la Rosette showed that static variables, such as a severe IPSS, poor Qmax, an enlarged prostate and BOO on pressureflow study, were risk factors for treatment failure. 13 They also showed that a higher PSA value and larger PV resulted in a greater risk of BPH-related invasive therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Büyük prostat ve yüksek PSA düzeyi olan kişilerde tek başına alfa bloker ajanların yetersiz kaldığı gösterilmiştir (20). Alfa bloker ile tedavi başarısızlığı prostat volümü 40 ml üzerinde ise %72, 40 ml altında ise %48 bulunmuştur (21).…”
Section: Bph'nın Progresyonunu öNgörebilir Miyiz?unclassified
“…Smooth muscle tone in the bladder, prostatic urethra, prostate gland, and prostatic capsule is the dynamic component and accounts for up to 40% of the obstruction seen in BPH (de la Rosette et al 2002). The static component of bladder outlet obstruction is prostate enlargement characterized by the increase in total volume and the transitional zone volume of the prostate gland.…”
Section: Table 1 | Evidence Base Included In the Reviewmentioning
confidence: 99%